PERAN AKUNTAN FORENSIK DAN TEKNIK AUDIT INVESTIGATIF DALAM PENGUNGKAPAN FRAUD DI INDONESIA - Nur Shihatus Sakinah (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
In Indonesia there are still many frauds in financial management. Therefore, this study aims to reveal the role of forensic accountants and investigative audit techniques in disclosing fraud in Indonesia. This research is qualitative with data collection methods using literature studies. The object of this study is secondary data in the form of fraud, using data obtained in the form of literature in the form of journals, books, online reading and other literary references related to the Role of Forensic Accountants and Investigative Audit Techniques in Fraud Disclosure in Indonesia. The findings in this literature study conclude that the Forensic Accountant plays an important role in disclosing cases of fraud, because the Forensic Accountant can find initial indications (indications of fraud) of the occurrence of fraud in an institution/company. The task of the Forensic Accountant when fraud has occurred is to detect it. Fraud can be detected by 2 techniques, namely: Critical Point Auditing (CPA) and Job Sensitivity Analysis (JSA). In disclosing fraud in Indonesia, the role of the Forensic Accountant is more prominent in the public sector than in the private sector, the reason being that most of the problems faced by the private sector are resolved outside the courts. One of the techniques used by Forensic Accounting in uncovering cases of fraud in an institution/agency is to conduct an investigative audit of criminal acts. The purpose of Investigative Audit is to identify and uncover fraud or crime.